O justo de Rawls na tributação da receita da exportação indireta, através das contribuições sociais - Lucas Silva Shikida (2018)
This dissertation aimed to investigate the definition of the element fair within the tax space, according to John Rawls' theory of justice. Specifically, we tried to find out if Rawls's contractual model, in relation to the tax and taxpayer, permits uncompensated taxation with certain legal dictates; the verification of the concept of fairness against direct and indirect exports and if there is plausibility of the reflexive equilibrium as an instrument of correction. The analyzes started from the hypothesis that the resolution is the use of the reflexive equilibrium. Within this procedure, the public agents involved in the administrative, judicial and legislative scope, based on the public conception of justice, will review the interpretive position of the tax immunity in focus. The investigation and bibliographical revision concerning the philosophical and tributary aspect and the logical and grammatical methods addressing the legislations correlated to the theme were investigated. It was tried to identify in the legal literature, the elements of Rawlsian theory and the tributary technical items that answer the proposed objectives. The research problem is due to the fiscal aspect of the State governed by the National Tax System based on the incidence of social security contribution on gross revenue in indirect exports, which are provided in the rule of art.149, §2 of the 1988 Federal Constitution. It should be noted that although the paradox between taxation is undue and at the same time it reverts to the social fund of the State, this misrepresents the structure of principles elaborated by Rawls, making the social security contribution on gross revenue in indirect exports unfair.